1996
DOI: 10.1074/jbc.271.48.30619
|View full text |Cite
|
Sign up to set email alerts
|

Carboxypeptidase E Activity Is Deficient in Mice with the fat Mutation

Abstract: Carboxypeptidase E (CPE) is involved in the biosyn

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

4
117
0

Year Published

1997
1997
2016
2016

Publication Types

Select...
8
2

Relationship

5
5

Authors

Journals

citations
Cited by 160 publications
(121 citation statements)
references
References 33 publications
4
117
0
Order By: Relevance
“…CPE is a key enzyme in the insulin secretory pathway, and disruptions in this pathway are known to alter the function and survival of pancreatic ␤-cells, and to cause diabetes in humans and animals (37,38). In the CPE fat/fat mouse strain, a single point mutation in CPE is sufficient to produce an animal with multiple disorders including obesity and diabetes (28,39). Importantly, one study found CPE polymorphisms associated with type 2 diabetes in humans (40).…”
Section: Discussionmentioning
confidence: 99%
“…CPE is a key enzyme in the insulin secretory pathway, and disruptions in this pathway are known to alter the function and survival of pancreatic ␤-cells, and to cause diabetes in humans and animals (37,38). In the CPE fat/fat mouse strain, a single point mutation in CPE is sufficient to produce an animal with multiple disorders including obesity and diabetes (28,39). Importantly, one study found CPE polymorphisms associated with type 2 diabetes in humans (40).…”
Section: Discussionmentioning
confidence: 99%
“…The mutant CPE is inactive and is rapidly degraded prior to transport into the Golgi (29). Without active CPE, the Cpe fat /Cpe fat mice have greatly elevated levels of peptide processing intermediates with C-terminal basic residues, and reduced levels of the fully processed peptides (28,30,31). However, low levels of mature peptides are detected, indicating that another enzyme is able to partially compensate for the absence of CPE activity.…”
mentioning
confidence: 89%
“…Obese Cpe fat /Cpe fat mice suffer from hyperproinsulinemia associated with expression of a mutated CPE, which results in destruction of the CPE protein in the rough endoplasmic reticulum (20,21). The pancreatic ␤-cells of these mice are clearly granulated but the content of the granules appears to be less dense (20), suggesting storage of proinsulin instead of mature insulin.…”
mentioning
confidence: 99%